MENINGKATKANKEMAMPUAN MOTORIK KASARANAK MELALUI GERAK DAN LAGU USIA 5 – 6 TAHUN DI TKPGRI MARANGKAYU TAHUN AJARAN 2017/2018 - Rikha - Kusmalia; Hanita - Hanita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
This study aims to improve 5-6 year old students’ gross motor skill through song and movement in PGRI Kindergarten Marangkayu, as well as, to revel and explain the obstacles and supporting factors.The main theory referred in this study is based on curriculum 2013 about early childhood education, regarding to the characteristics of teaching young learnes ; 1) develop learner’s development optimally which covers the aspect of religious and moral value, physical-motor skill, attitude, knowledge, and skill; 2) apply thematic learning and scientific approach in stimulating education; 3) use authentic assessment in observing learner’s development , and 4) empower parents’ rolein learning process.The researcher conducted a classroom action research which involved students of PGRI Kinfergarten as the research subjects. The learning activity carried out by the researcher was by using movement and songs during two cycles, wherein each cycle consists of three mettings.The result of analysis show that the activity of song snd movement managed to improve students’ gross motor skill, which can be seen in the recapitulation of percentage of students’ gross motor skill assessment. At cycle 1, the average score was 53,7%, meanwhile, in cycle 2, becoming 97,9%